Quality of life in the older adults: The protective role of self-efficacy in adequate coping in patients with chronic diseases - Cudris-Torres, Lorena; Alpi, Stefano Vinaccia; Barrios-Núñez, Álvaro; Gaviria Arrieta, Natali; Mejía Gutiérrez, Jéssica; Alvis Barranco, Libia; Rios-Carlys, Gerson; Cuenca-Calderón, Silvia E.; Bermúdez, Valmore; Hernández-Lalinde, Juan; Riveira Zuleta, Carlos Arturo; Bahamón, Marly Johana; et al. (Frontiers in Psychology, 2023)
The purpose of the present study was to establish the relationships between self-efficacy, perception of disease, emotional regulation, and fatigue and the health-related quality of life in older adults living in the departments of Cesar and Atlántico in Colombia and who have been diagnosed with a chronic disease. The participants were 325 older adults of both sexes, with literacy skills and no presence of cognitive impairment. We used the MOS-SF-36 questionnaire, the Brief Illness Perception Questionnaire scale for measuring the perception of disease, the Stanford Patient Education Research Center's Chronic Disease Self self-efficacy questionnaire for chronic patients, the Difficulties in Emotional Regulation Scale, and the Fatigue Severity Questionnaire as measurement instruments. The design was non-experimental cross-sectional with a correlational scope. The results indicated that the physical function of quality of life, self-efficacy, disease perception, emotional regulation, and fatigue severity were relevant predictors, confirming that self-efficacy could be a protective factor, decreasing the probability of a participant obtaining low scores in this quality-of-life aspect. In contrast, both disease perception and fatigue severity were identified as risk variables.